“Psychological Injuries Are Not Visible”: Experiences and Perceptions of Midwives and Nurses about Domestic Violence during Pregnancy - Simsek-Cetinkaya, Şahika; Evrenol Ocal, Simge (SAGE Publications, 2023)
This study aimed to describe perceptions and experiences of nurses and midwives working in primary care about domestic violence (DV) in pregnancy. Data were collected by conducting in-depth face-to-face interviews with 10 midwives and 7 nurses working in seven family health centers between July 17 and August 28, 2020. Five main themes emerged: “The causes of domestic violence,” “Difficulty recognizing domestic violence,” “Obstacles to revealing domestic violence,” “Obstacles to Assisting/Supporting domestic violence in pregnant women,” and “Solutions to prevent domestic violence in pregnancy.” Midwives/nurses feel inadequate and unprepared to recognize the symptoms of DV and to guide and support women and they are willing to take an active role in managing DV. It is recommended that they should be trained on DV, a monitoring system should be established including primary healthcare services and a measurement tool should be developed.
Keywords: Domestic Violence; Pregnancy; Attitude of Health Personnel; Humans; Nurses; Female; Prenatal Care; Midwifery; Nurse-Patient Relations; 5. Gender equality; 3. Good health